IMPLEMENTASI METODE NAÏVE BAYES DALAM PERANCANGAN SISTEM PENUNJANG KEPUTUSAN PENINGKATAN POLA HIDUP SEHAT BERBASIS ANDROID - Hartatik M.Si.; Putri K Wardhani (Universitas Sebelas Maret, 2017)
Health is the need of every individual, but because of too high busyness that has not been conscious and optimal to live a healthy lifestyle. Healthy lifestyle is the best choice that can be done to keep the body healthy. In this case pernanan information technology as a great source of information in support of healthy lifestyle arrangement. One of them is the expert system as a personal communication media for each person to help the process of healthy lifestyle arrangement.The design of the system is built quickly Web and web-based web applications are expected to help people in making decisions to improve healthy lifestyle and information about health and body care. This system provides recommendations on the menu or foods that are suitable for a healthy lifestyle program (diet). This decision support system is developed by the method of observation, data completion, data analysis, design and design. This decision support system uses the Bayes theorem concept and is built using HTML, CSS, and Java Script programming languages for features, and the PHP programming language (Hypertext Preprocessor) for web programming.Keywords: bayes, Bayesian, java, SPK, naïve bayes, diet